SCN8A mutations in Chinese patients with early onset epileptic encephalopathy and benign infantile seizures - Jiaping Wang; Hua Gao; Xinhua Bao; Qingping Zhang; Jiarui Li; Liping Wei; Xiru Wu; Yan Chen; Shujie Yu (BMC, 2017)
Abstract Background SCN8A mutations have recently been associated with epilepsy and neurodevelopmental disorders. This study aimed to broaden the phenotypic-spectrum of disease related with SCN8A mutations. Methods To identify the pathogenic gene of a Chinese family, in which six members suffered from epilepsy, whole-exome sequencing was performed. In addition, target next-generation sequencing (NGS) was performed on 178 sporadic patients, who had epilepsy of unknown etiology within 6 months after birth. A detailed clinical history was obtained. Results A heterozygous missense mutation of SCN8A was identified in the Chinese family. Six de novo mutations of SCN8A were detected in 6 sporadic patients with epilepsy. In the family, six members developed seizures within a few years after birth. Five of them had milder clinical performance, that they had normal cognition and developmental milestones, and seizure-free was achieved by mono-therapy. The other one affected member presented with refractory epilepsy and developmental regression. She died from sudden unexpected death in epilepsy (SUDEP) at 17-year-old. Clinical features of six sporadic patients with SCN8A mutations were diverse, ranging from severe epileptic encephalopathy to benign epilepsy with normal cognition. Seizures started at the mean age of 3.9 months (from 2 months to 6 months). Seizure-free was achieved in four of them by mono- or multi-antiepileptic drugs. Five of them demonstrated mild or severe psychomotor retardation, whereas the other one was normal in development and intelligence. Conclusions Our findings extend the spectrum of SCN8A mutations and the clinical features of patients with SCN8A mutations. The majority of SCN8A mutations were de novo, inherited mutations from the heterozygous parents can also occur. The phenotypic spectrum of SCN8A mutation varied largely. Most affected patients manifested as refractory epilepsy and severe intellectual disability, only a small number of patients presented with milder clinical patterns. Additionally, our study confirmed that the same mutation can lead to different phenotypes.